Channel response in structurally disturbed terrain: evaluation of implication of neotectonic activity through an integrated approach - Vijith, Vijith; Prasannakumar, V.; Mohan, M.; Pratheesh, P. (Taylor & Francis Ltd., 2015)
The anomalous channel pattern in the midland stretch of the river Karamana, having highly sinuous and incised course with varying floodplain, is analysed to determine the different stages of evolution of the river channel in response to the structural disturbances in the area. Geometric analysis of foliation, geospatial analyses of sinuosity index, hypsometry, channel and streamline changes, river channel cross-profile, longitudinal profile and derivation of fold structure from satellite images were attempted in evaluating the characteristic features of the selected river segment. Datasets used in the analysis were collected through the detailed fieldwork, structural mapping and interpretation of satellite images and satellite-derived digital elevation data. Systematic analysis of the channel pattern of the selected reaches of the river, in 1915, 1968 and 2008 classifies the river as tortuously meandering. Implications of tectonic disturbance can be inferred from the presence of channel incision, unpaired terraces, younger terrain with intense erosion, knick points, convex river long profile, and high hypsometric integral, oscillating and unpaired character of the river channel. Structural analysis along with GIS and remote sensing studies proved the presence of a major fold with a NW–SE-trending axial surface. An evolutionary model is proposed to elucidate the channel planform changes in response to the deformation and tectonic uplift of the region.